Application of Emulsion Liquid Membrane Process for Cationic Dye Extraction - Mohammed, Manal Adnan; Noori, Wasan Omar; Sabbar, Huda Adil (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
In the present work studies were carried out to extract a cationic dye (Methylene Blue MB) from an aqueous solution using emulsion liquid membrane process (ELM). The organic phase (membrane phase) consists of Span 80 as emulsifier, sulfuric acid solution as stripping agent and hexane as diluent. In this study, important factors influencing the extraction of methylene blue dye were studied. These factors include H2SO4 concentration in the stripping phase, agitation speed in the dye permeation stage, Initial dye concentration and diluent type.   More than (98%) of Methylene blue dye was extracted at the following conditions: H2SO4 concentration (1.25) M, agitation speed (200) rpm, dye concentration (10) ppm and the diluent type was hexane.